2015
DOI: 10.1007/978-3-319-10756-1
|View full text |Cite
|
Sign up to set email alerts
|

Solid Surfaces, Interfaces and Thin Films

Abstract: Graduate Texts in Physics publishes core learning/teaching material for graduate-and advanced-level undergraduate courses on topics of current and emerging fields within physics, both pure and applied. These textbooks serve students at the MS-or PhD-level and their instructors as comprehensive sources of principles, definitions, derivations, experiments and applications (as relevant) for their mastery and teaching, respectively. International in scope and relevance, the textbooks correspond to course syllabi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 18 publications
0
31
0
5
Order By: Relevance
“…So the substrate is not playing an important role in this matter, but while looking toward the Si wafer, it is observed that there is a difference in the value of surface roughness as compared to the other two substrates. The reason probably is the abrupt change in the interface between the substrate and the SiO film (crystalline/amorphous) (Lüth 2001) as compared to other substrates, i.e., glass and PEN, which has amorphous/amorphous interface.…”
Section: Ibd Layer Analysis On Pen Substratementioning
confidence: 99%
“…So the substrate is not playing an important role in this matter, but while looking toward the Si wafer, it is observed that there is a difference in the value of surface roughness as compared to the other two substrates. The reason probably is the abrupt change in the interface between the substrate and the SiO film (crystalline/amorphous) (Lüth 2001) as compared to other substrates, i.e., glass and PEN, which has amorphous/amorphous interface.…”
Section: Ibd Layer Analysis On Pen Substratementioning
confidence: 99%
“…Nanotubes of very narrow, but finite thickness may be achieved in few different ways. In the case of quantum wires built of narrow-gap materials surface states may induce Fermi level pinning above the conduction band edge which results in accumulation of electrons in the vicinity of the surface [1]. Nowadays it has become feasible to combine two (or even more) different materials into one vertical structure, i.e., coreshell nanowires (CSNs).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the reciprocal lattice vectors, a * i , are defined in terms of the real space lattice vectors, a i , by the following relationship [1]:…”
Section: (22)mentioning
confidence: 99%
“…Fig. B.1B, lower 1 Single layers of graphene are visible under the optical microscope when deposited on oxidized Si substrates with very defined thickness. In this case, single carbon layers can be distinguished by slightly changing the optical path length of the transmitted light in comparison to the empty substrate.…”
Section: A6 Reproducibility Of the Measurementsmentioning
confidence: 99%
See 1 more Smart Citation